2011
DOI: 10.1056/nejmicm1006530
|View full text |Cite
|
Sign up to set email alerts
|

Palmar–Plantar Rash with Cytarabine Therapy

Abstract: images in clinical medicineT h e n e w e ng l a n d j o u r na l o f m e dic i n e n engl j med 364;3 nejm.org january 20, 2011 e5 A 52-year-old man with acute myeloid leukemia underwent induction chemotherapy consisting of a 7-day intravenous infusion of cytarabine plus daunorubicin on days 1 through 3. Bone marrow biopsy performed on day 14 revealed that blast cells still accounted for 60 to 80% of the total cells in the marrow, indicating an inadequate response to initial induction therapy. Intermediate-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…A few cases have shown that intermediate-to-high doses of cytarabine can lead to PPE. 10,11 The potential interaction between cytarabine and posaconazole could increase the development of this rare adverse effect. A study with various cytarabinecontaining regimens have utilized posaconazole prophylaxis without experiencing PPE.…”
Section: Discussionmentioning
confidence: 99%
“…A few cases have shown that intermediate-to-high doses of cytarabine can lead to PPE. 10,11 The potential interaction between cytarabine and posaconazole could increase the development of this rare adverse effect. A study with various cytarabinecontaining regimens have utilized posaconazole prophylaxis without experiencing PPE.…”
Section: Discussionmentioning
confidence: 99%
“…After 20 days the skin disorders had spontaneously disappeared. Reproduced with permission from [34], © Massachusetts Medical Society (2011).…”
Section: Micellesmentioning
confidence: 98%
“…These drugs include the topoisomerase I inhibitor camptothecin [68], the topoisomerase II inhibitor doxorubicin [69], the DNA damaging agents cisplatin and doxorubicin [70], γ-irradiation [71], and the anti-metabolite cytarabine [72]. These observations suggest that different drugs may activate senescence through different signaling pathways.…”
Section: Therapy-induced Senescence (Tis) a Double-edged Sword?mentioning
confidence: 99%